Experimental Conditions That Influence the Utility of 2'7'-Dichlorodihydrofluorescein Diacetate (DCFH2-DA) as a Fluorogenic Biosensor for Mitochondrial Redox Status - Lianne R. de Haan; Megan J. Reiniers; Laurens F. Reeskamp; Ali Belkouz; Lei Ao; Shuqun Cheng; Baoyue Ding; Rowan F. van Golen; Michal Heger (MDPI AG, 2022)
Oxidative stress has been causally linked to various diseases. Electron transport chain (ETC) inhibitors such as rotenone and antimycin A are frequently used in model systems to study oxidative stress. Oxidative stress that is provoked by ETC inhibitors can be visualized using the fluorogenic probe 2',7'-dichlorodihydrofluorescein-diacetate (DCFH2-DA). Non-fluorescent DCFH2-DA crosses the plasma membrane, is deacetylated to 2',7'-dichlorodihydrofluorescein (DCFH2) by esterases, and is oxidized to its fluorescent form 2',7'-dichlorofluorescein (DCF) by intracellular ROS. DCF fluorescence can, therefore, be used as a semi-quantitative measure of general oxidative stress. However, the use of DCFH2-DA is complicated by various protocol-related factors that mediate DCFH2-to-DCF conversion independently of the degree of oxidative stress. This study therefore analyzed the influence of ancillary factors on DCF formation in the context of ETC inhibitors. It was found that ETC inhibitors trigger DCF formation in cell-free experiments when they are co-dissolved with DCFH2-DA. Moreover, the extent of DCF formation depended on the type of culture medium that was used, the pH of the assay system, the presence of fetal calf serum, and the final DCFH2-DA solvent concentration. Conclusively, experiments with DCFH2-DA should not discount the influence of protocol-related factors such as medium and mitochondrial inhibitors (and possibly other compounds) on the DCFH2-DA-DCF reaction and proper controls should always be built into the assay protocol.